Evaluation of Clinical Marginal Adaptations of the Copings Fabricated in Cad Cam - Retrospective Study - Rithanya.P1 , Subhashree.R2 , (Institute of Medico-legal Publications Pvt Ltd, 2020)
CAD CAM Technology is a computer aided design and manufacturing system for the production of crowns.A variety of metal and all ceramic materials is available for the crown fabrication. The accuracy and the fit ofthe prosthesis depends on the CAD CAM system and each component individually like the milling and thescanner units. The aim of the present study was to determine the marginal adaptations of copings fabricatedwith CAD CAM and to analyse which technique has been used commonly to check the marginal fit of thecopings. The study was carried out on a hospital setting with ethical approval. The records of the patientswere collected and Chi square test was done to evaluate the results. From the overall study, it was found thatthere were different methods for the evaluation of fit of the copings. Most of the FPD patients were in theage group of 26 to 40 years. Most common method for checking marginal fit adaptation was RVG/IOPA. (pvalue =0.37) which is not statistically significant, followed by the catching on probing and the fit checker.